Origin and molecular evolution of the plastid - Bhattacharya, Debashish (Henry Stewart Talks, 2007)
Plastid distribution in eukaryotes, Tree of life, Evidence for plastid origin through endosymbiosis, Primary, secondary and tertiary endosymbiosis, Organelle genome evolution, Endosymbiotic gene transfer, Dating the origins of plastids